Pengujian Efektivitas Pupuk Kulit Bawang Merah Dan Pupuk Kandang Terhadap Pertumbuhan Bawang Daun - Amelia, Salsa; Indriasari, Rahayu; Septiani, Delia; Rahma, Elita; Adha, Mawar Nurul; Rozak, Rama Wijaya Abdul; Sugiarti, Yatti (Jurnal Sosiologi Pertanian dan Agribisnis, 2023)
Onion skin is often a problem of waste in households because of the low level of public understanding of how to utilize onion skin waste. Onion skin waste can be used as a mixed fertilizer that can accelerate plant growth because it contains compounds and substances that provide fertility. In addition to liquid fertilizer, there is manure that can be used in the process of plant growth to replace inorganic fertilizers. This study aims to determine the comparison of the effectiveness between shallot skin fertilizer and manure on leek plants. Onion (Allium fistulosum L.) is a vegetable commodity that has high economic value. The research method used is experimentation which is a method in quantitative research by examining cause and effect and comparing the results of each component. The parameters observed were plant height and the number of leaves that grew on the leek plants. The results of this study indicate that the difference in effectiveness between liquid onion skin fertilizer and manure has a significant effect on leek plants.